Baṅgabandhura cintādhārā o Bākaśālera bhūmikā - Phāruka, Esa. Ema (Esa. Ema. Phāruka, 1981)
Political philosophy of Sheikh Mujibur Rahman, 1922-1975, former president of Bangladesh, with reference to his introduction of a single party, Bamladesa Krshaka Sramika Aoyami Liga (BAKSAL), political system in Bangladesh.